Edukasi Gerakan 3R (Reduce, Reuse, Recycle) Kepada Siswa SDS Midori Cikarang Selatan : Indonesia - Irwati, Dwi; Dafid Kholik; Madania Iklimaturriza; Wanda Gilang Ramadhan; Imam Prasetyo (DPPM Universitas Pelita Bangsa, 2023)
A clean and healthy environment is the most basic thing for every living thing. To create a clean and healthy environment in our environment, it is necessary to equip or instill education on the reduce, reuse and recycle movement for a clean Indonesia or commonly called the 3R movement. Especially equipping the clean Indonesia movement from an early age at the elementary school level. The provision of the 3R movement is expected to be able to prepare excellent human resources who care for a clean and healthy environment. The purpose of this research is to design and document the provision of the 3R movement for a clean Indonesia at Midori Cikarang Selatan Elementary School. The debriefing is designed in 3 stages, namely preparation, implementation, and evaluation. The results of this training are expected for each individual not to litter which can cause environmental pollution, ecosystem damage, natural disasters, and disease. Keywords: 3R, Education, Environment, Waste